Production of a Highly Immunogenic Antigen from SARS-CoV-2 by Covalent Coupling of the Receptor Binding Domain of Spike Protein to a Multimeric Carrier - Argentinian AntiCovid Consortium (2021)
Since the discovery of SARS-CoV-2, several antigens have been proposed to be part of COVID-19 vaccines. The receptor binding domain (RBD) of Spike protein is one of the promising candidates to develop effective vaccines since it can induce potent neutralizing antibodies. We previously reported the production of RBD in Pichia pastoris and showed it is structurally identical to the protein produced in mammalian HEK-293T cells. In this work we designed an RBD multimer construct with the purpose of increasing RBD immunogenicity. We produced multimeric particles by a transpeptidation reaction between the RBD expressed in P. pastoris and Lumazine Synthase from Brucella abortus (BLS), which is a highly immunogenic and very stable decameric protein of 170 kDa. We vaccinated mice with two doses 30 days apart, and then we measured humoral immune response. When the number of RBD copies coupled to BLS was high (6-7 RBD molecules per BLS decamer, in average), the immune response was significantly better than that elicited by RBD alone or even by RBD-BLS comprising low number of RBD copies (1-2 RBD molecules per BLS decamer). Remarkably, the construct with high number of RBD copies induced high IgG titers with high neutralizing capacity. Furthermore, a superior immune response was observed when Al(OH)3 adjuvant was added to this formulation, exhibiting a higher titer of neutralizing antibodies. Altogether our results suggest that RBD covalent coupled to BLS forming a multimer-particle shows an advantageous architecture to the antigen-presentation to the immune system which enhances immune responses. This new antigen should be considered a potent candidate for a protein-based vaccine.